The nationalization of politics : the formation of national electorates and party systems in Western Europe - Caramani, Daniele, 1968- (Cambridge studies in comparative politics., 2004)
In an in-depth comparative and long-term analysis, first published in 2004, Daniele Caramani studies the macro-historical process of the nationalization of politics. Using a great wealth of data on single constituencies in seventeen West European countries, he reconstructs the territorial structures of electoral support for political parties, as well as their evolution since the mid-nineteenth century from highly fragmented politics in the early stages toward nation-wide alignments. Caramani provides a multi-pronged empirical analysis through time, across countries, and between party families.